MORTALITAS DAN PROFIL HEMATOLOGI MENCIT YANG DIINFEKSI Trypanosoma evansi ISOLAT BANGKALAN, PEMALANG DAN PIDIE - Didik T Subekti; Mutiara Febria; Febiola Rama Sari; Indri N Hartiyati (BERITA BIOLOGI, 2013)
Trypanosoma evansi known as trypanosomiasis causes or called surra in animals. Trypanosomiasis-associated death were generally due to severe anemia. Another report mentioned that a rapid death of mice can be attributed to the several reasons. One of those reasons is highly parasitaemia that leads to death of the host. However, there is another distinct report that high parasitemia in mice does not necessarily lead to anemia and clinical symptoms. This research was focused to study the relationship between trypanosomiasis-associated death with haematology profile, particularly the decrease of PCV (packed cell volume) value, anemia and virulence of T. evansi collected from several region of Indonesia. The experiments were performed by dividing mice into four groups. Three groups were infected by T.evansi according to the original isolates while another group were uninfected mice. Every two-day interval, all mice were observed their mortality and parasitaemia and also examined the PCV value and erythrocyte counts in peripheral blood. The experimental results shown that the degree of parasitemia in mice were not always related to mice mortality and anemia. Decreases of PCV value were related to the existence of parasitaemia but not with anemia. This study suggests that there is no relationship between the decreases of PCV value and anemia to the trypanosomiasis-associated death in mice.